First records of giant pill-millipedes from Laos (Diplopoda, Sphaerotheriida, Zephroniidae) - Wesener, Thomas (Zootaxa, 2019)
Before this study, giant pill-millipedes (order Sphaerotheriida) were unknown from Laos despite their presence in all surrounding countries. As by-catch from collections by arachnologists, 31 specimens of Sphaerotheriida from Laos became available for study. The sample included 14 species. Three species were only represented by females, which are described but cannot be named. Of the remaining 11 species, a single species belongs to the genus Zephronia Gray, 1832: Z. laotica n. sp.; and the other ten belong to the genus Sphaerobelum Verhoeff, 1924: S. bolavensis n. sp., S. phouloei n. sp., S. denticulatum n. sp., S. spinatum n. sp., S. lachneeis n. sp., S. peterjaegeri n. sp., S. nigrum n. sp., S. splendidum n. sp., S. laoticum n. sp., and S. schwendingeri n. sp. This more than doubles the known diversity of Sphaerobelum. Here, I integratively describe these species, combining morphology and DNA barcodes with a molecular analysis including all Zephroniidae species deposited on GenBank—including the only giant pill-millipede species known from Cambodia, Zephronia dawydoffi Attems, 1953. An updated determination key to the species of the genus is presented. Zephronia laotica n. sp. belongs to the monophyletic Zephronia sensu stricto group, which is confirmed by molecular barcoding. In contrast, most species of Sphaerobelum are in a weakly supported clade. Genetically, Sphaerobelum species differ greatly from one another, with most p-distances >15%. The lowest observed p-distance (9.8%) is between S. truncatum Wongthamwanich et al. 2012 from Thailand and S. peterjaegeri n. sp.